A Charge‐Transfer‐Induced Self‐Healing Supramolecular Hydrogel. Issue 23 (28th October 2016) - Gao, Lei; Gao, Yuxia; Lin, Yuan; Ju, Yong; Yang, Song; Hu, Jun
Abstract: In this study, a dual‐component charge‐transfer (CT)‐induced supramolecular hydrogel was fabricated using pyrene‐tailored pyridinium (PYP) and 2, 4, 7‐trinitrofluorenone (TNF) as the electron donor and acceptor, respectively. Its thermal stability and mechanical property have been modulated effectively by altering the concentration or molar ratio of PYP and TNF. Moreover, this CT hydrogel exhibited a distinct injectable self‐healing property that could be utilized to create desired patterns on substrates. Such property holds potential for this CT hydrogel in fields like three‐dimensional printing and surface coating. Abstract : Time to heal : A dual‐component charge‐transfer (CT)‐induced supramolecular hydrogel was fabricated by using pyrene‐tailored pyridinium (PYP) and 2, 4, 7‐trinitrofluorenone (TNF) as the electron donor and acceptor, respectively (see scheme). This hydrogel exhibited a distinct injectable self‐healing property that could be utilized to create desired patterns on substrates, which holds potential in fields like three‐dimensional printing and surface coating.